Estudo comparativo entre a utilização real e a determinada pelo planejamento da mecanização agrícola em empresas rurais de soja e arroz - Ereno, Luis Henrique Zibikoski (2008)
The objective of this thesis was to carry out a study comparing actual utilization in rural businesses of soy and rice to that which is determined by agricultural mechanization planning. In this context, the specific objectives were as follow: to gather information about the composition of the agricultural machinery market; to establish a relationship between the number of tractors distributed over areas and crops; to determine the mechanization index (kW. ha-1) of rural businesses in relation to area and crop, thus establishing a comparison between that which is planned technically and that which actually occurs; to analyze the lifetime of the fleet of tractors; to verify the state of conservation of existent agricultural tractors in the rural businesses used in this study and develop a worksheet for dimensioning and selection of agricultural machines. Twenty-two rural businesses in the central region of the state of Rio Grande do Sul with areas greater than 50 hectares that exclusively developed rice or soy crops were sampled. The systematic random technique was utilized for localization of data gathering points. The adapted method of Schlosser (1998), called Step by step was used for the dimensioning of the machines and planning of activities. This method is developed on worksheets, and in this case, utilizing Microsoft Excel. It was concluded that the market of agricultural tractors is led by Massey Ferguson, followed by New Holland, Valtra and John Deere, respectively. Rice businesses presented a greater number of tractors per area and a mechanization index superior to that of soy businesses. The mean real mechanization index was superior to that for technical planning, both for rice and soy businesses, proving the existence of an excess of potency and demonstrating the viability of adopting planning tools in the selection of agricultural machinery, in order to optimize the use of machinery in these crops. The fact that rice crops presented a greater number of tractors per area when compared to soy crops was due to the fact that there are a greater number of operations involved and these are concentrated during the period close to harvest. The mean lifetime tractors in the central region of Rio Grande do Sul was 14.82 years. The state of conversation of the tractors decreased with the age of the tractor. In rice businesses, this wear-out is anticipated because of the operating conditions.